Tauhid dan Moral Sebagai Karakter Utama dalam Pendidikan Islam - Arifah, Amirah; Sinaga, Silvi Fauziah; Pasaribu, Rahmat (Integrasi: Jurnal Studi Islam dan Humaniora, 2024)
Tawhid and morality are two key concepts in Islam that shape the character and values of Muslims. Tawhid, as the concept of the oneness of God, includes aspects of rububiyah, uluhiyah, and asma' wa shifat, which teaches belief in the oneness of God in creation, worship, and His attributes and names. Moral, or akhlak, refers to behavior and character in accordance with Islamic teachings, covering interpersonal, intrapersonal, and human relationships with God. This article uses a library research method by using several journal references and also books that discuss tawhid and morals as the main character inÂ Islamic education. Similarly, moral education in Islam aims to form good character, by teaching values such as gratitude, monotheism, establishing prayer, amar ma'ruf nahi munkar, and being patient. Through understanding and implementing the concepts of monotheism and morality, Muslims are expected to be able to obtain life guidance in accordance with religious teachings, form a solid character, and contribute positively to fostering a harmonious and moral society.